Thermodynamical consistency of quasiparticle model at finite baryon density - Ma, Hong-Hao [UNESP]; Lin, Kai; Qian, Wei-Liang [UNESP]; Hama, Yogiro; Kodama, Takeshi (Amer Physical Soc, 2019)
In this work, we revisit the thermodynamical self-consistency of the quasiparticle model with the finite baryon chemical potential adjusted to lattice QCD calculations. Here we investigate the possibility that the effective quasiparticle mass is also a function of its momentum k, in addition to temperature T and chemical potential mu. It is found that the thermodynamic consistency can be expressed in terms of an integrodifferential equation concerning k, T, and mu. We further discuss two special solutions, both can be viewed as a sufficient condition for the thermodynamical consistency, while expressed in terms of a particle differential equation. The first case is shown to be equivalent to those previously discussed by Peshier et al. The second one, obtained through an ad hoc assumption, is an intrinsically different solution where the particle mass is momentum dependent. These equations can be solved by using boundary condition determined by the lattice QCD data at vanishing baryon chemical potential. By numerical calculations, we show that both solutions can reasonably reproduce the recent lattice QCD results of the Wuppertal-Budapest and HotQCD Collaborations, and in particular, those concerning finite baryon density. Possible implications are discussed.